Electrically injected double‐taper semiconductor laser based on parity‐time symmetry. Issue 5 (16th December 2021) - Wang, Xueyou; Li, Jing; Fu, Ting; Chen, Jingxuan; Dai, Yingqiu; Han, Renbo; Wang, Yufei; Zheng, Wanhua
Abstract: An electrically injected semiconductor laser based on parity‐time symmetry with a double‐taper structure is fabricated and measured. The double‐taper semiconductor lasers are defined by contact‐type standard photolithography and then etched by inductively coupled plasma. The double‐taper parity‐time‐symmetric laser can obtain an output power of more than 0.5W @0.3A, which is significantly higher than the 0.35W@0.3A of the traditional single‐ridge laser. The parity‐time‐symmetric breaking point or exceptional point is tuned below lasing threshold to get narrower linewidth compared with traditional single‐ridge lasers and double‐ridge lasers, and performs single‐lobe far field.